The Victorian mood in the tropics : a socio-cultural analysis of the practice and position of science in British Malaya, 1877-1990 - Mohd Helmi Bin Mohd Sobri (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2010)
This study investigates and examines the practice and position of science in British Malaya, from 1877 until 1900. Basically it is based on the approach of socio-cultural history known as the history of mentalities. Through this approach, a balanced emphasis is given to social conditions, cultural values, imbued in unspoken assumptions and perceptions, and their relations to conscious intellectual endeavors and institutional set-up. The significance of this study rests on few findings that revolve around three main themes. The first theme is on SBRAS, where it argues that the foundation of SBRAS in 1877 signifies the first self-conscious collective endeavor in scientific activity in British Malaya. Then, this study gives justification for the significance of SBRAS in enlarging space for scientific discourse in the colonial public sphere. The second theme is on the role of environment as socio-spatial setting in shaping attitudes towards nature and thus defines the possible forms of scientific activity. Based on the comparison between the experience in the Malay States and Singapore, this study shows the way how environment had influenced the mode of scientific practice and consciousness. The last theme is on the significance and limitation of public institutions like Museum and Botanic Garden, in sustaining scientific activism and image of the British colonies and protectorates in Malaya. By drawing few cases from Singapore, Perak and Selangor, this study concludes that these public institutions were important in enlarging the collection of scientific specimens, though at the same time they suffered from the lack of expertise to identify them. Finally, it argues that British Malaya had played a considerable role in trying to realize the dream of imperial science, through its financial and material support in sustaining the survival of Imperial Institute in London.